Educational seminar supervision and quality assurance through educational reports - Waska Warta; Ervin Aulia Rachman; Daris Yolanda Sari; Dita Humaeroh (Jurnal Scientia, 2024)
Understanding supervision, quality assurance, and educational reports is essential for School Principals in organizing quality education. Therefore, a community service project is planned through an Education Seminar with the theme "Supervision and Quality Assurance through Educational Reports" specifically designed for Elementary School Principals in Purwakarta Regency. Supervision and Quality Assurance in Education through Educational Reports aim to provide a platform for school principals and other stakeholders to explore, discuss, and formulate the integration of effective supervision and quality assurance practices using educational reports as the primary tool. A significant portion of the seminar was dedicated to the concept and practice of supervision in education. Supervision, as elucidated in the discussion, emerged as a collaborative and supportive endeavour led by school principals to enhance the professional development and performance of educators. The primary focus was on how effective supervision, particularly through sustained support programs, can identify and address the diverse needs of teachers, contributing to the overall improvement of educational quality.